Adam Zygmunt Czyżewicz (1841-1910) - a Distinguished Teacher of the Lviv Midwives School - Małgorzata Stawiak-Ososińska (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
This article is dedicated to life and activity of Adam Zygmunt Czyżewicz. He was the most distinguished teacher of the 19th-century history of the midwives school of Lviv. This progressive and devoted obstetrician reformed squalid institution intended for midwives education and he brought it to its heyday. In 1871, when he held a professor position, the school did not have its own accommodation and it was situated in a rented, neglected building which did not comply with basic didactic, sanitary and health requirements this type of institutions should meet. Study lasted only 5 months during which the future obstetric graduates were provided with elementary theoretical information (within the range of woman anatomical structure, labour physiology and childbirth irregularities, principles of birth assistance in case of various foetus presentations and methods of newly delivered mother and newborn baby care) and practical abilities. Providing the significant majority of students (often illiterate) in such short period of time with education for midwives was hardly possible. Czyżewicz began to seek the introduction of necessary changes which would help to transform the existing institution into a successful unit. Thanks to many efforts and incredible engagement of this community doctor, a modern maternity and gynaecological clinic was established. It had also school facilities for the future midwives. Study period was extended to 10 months, antiseptic principles education and observance were introduced. Thanks to these reforms, the school complied with the European standards within the scope of midwives educations and it became one of the best institutions of this type in Austria.